Embodied cognition driven Qigong: a cross-sectional study and a pilot randomized controlled trial on managing depression and preventing relapse in substance dependence - Chao Sun; Siyao Yang; Xiaojun Wang; Yongcong Shao; Xuetong Huang; Huanhuan Qi; Zhuolin Zhang; Guobai Su (Frontiers Media S.A., 2024)
ObjectiveSubstance use disorders (SUDs) pose a significant challenge to public health systems worldwide, with persistent high relapse rates underscoring the urgency for innovative intervention strategies. This study embarked on a systematic exploration of the factors influencing relapse among individuals with SUDs, alongside the implementation of targeted Health Qigong intervention to mitigate these effects based on the embodied cognition.MethodsIn the cross-sectional survey, a total of 398 male substance users were recruited to complete the questionnaires assessing depression, self-esteem, resilience, and relapse inclination. Subsequently, 60 participants diagnosed with depression were selected for a Pilot RCT, randomly divided into an intervention group, which underwent a 12-week Health Qigong program designed to combat depression through embodied cognition principles, and a control group, which maintained their daily routines.ResultsStructural equation modeling demonstrated that depression not only had a direct effect on substance users' relapse, but also exerted an indirect effect through three paths: firstly, via the mediating role of self-esteem; secondly, via the mediating role of resilience; and thirdly, via the chain-mediated role of self-esteem and resilience. Two-factor mixed-design ANOVA showed that the 12-week targeted Health Qigong training not only mitigated depression in individuals with SUDs, but also enhanced self-esteem and mental resilience, and reducing the propensity for relapse.ConclusionThis research identifies critical factors influencing relapse in individuals with SUDs and introduces a novel, non-pharmacological intervention that significantly diminishes relapse rates and enhances recovery outcomes. It highlights the importance of physical activity in promoting mental health improvement and integrates traditional Chinese exercises with contemporary psychological insights, offering a comprehensive approach to drug rehabilitation and the integration of cultural practices in holistic health interventions.